Multi-wavelength analysis of CME-driven shock and Type II solar radio burst band-splitting - Soni, Shirsh Lata; Ebenezer, E.; Yadav, Manohar lal (My University, 2021)
It is now well established that Coronal Mass Ejections (CMEs) may produce shocks in near Sun and interplanetary medium. A Type-II radio burst is characterized by shock and associated emission with very slow frequency drift rate (∼0.1 MHz/sec). A CME driven shock and their velocity, acceleration/deceleration signature can be observed by a Type-II solar radio burst which drifts with the shock speed and is split in bands of plasma radio emission. These emissions can be seen in radio spectrographs as split bands both in fundamental and harmonic frequencies close to a ratio of 1:2. In this paper, we present an analysis of a CME associated with a band splitting Type-II radio burst observed using multi-instruments in multi-wavelengths. We observed the CME event that occurred in 02 May 2013 (05:24 UT) and is associated with an M1.1 class solar flare from the active region NOAA 11731 located at N10W23 on the solar disk. We use the widely accepted Newkirk coronal density model to estimate the height in the solar atmosphere to compare our results. We conclude that the speed of CME is high enough to produce a Type-II solar radio burst. The analysis of this paper also involved an estimation of the coronal ambient magnetic field and its comparison with the empirical active region magnetic field model (Dulk and McLean in Sol. Phys. 57:279, 1978). This shows the good results. Observations provide sufficient evidence that the unusual patch signature in Type-II solar radio burst is due to the CME–CME interaction.
Keywords: Coronal Mass Ejection; Radio burst; Solar flare; Shock